Germany: Preparing for the Labour Market and Lifelong Learning - Weiß, Reinhold [Verfasser] (My University, 2012)
Germany has one of the lowest rates of youth unemployment in Europe and the world (8.0% in July 2012 compared to an EU average rate of 22.5%). This contribution argues that the main reason for the low level of youth unemployment is the close linkage between school-based and company-based learning in the dual system of vocational education and training (VET). One chapter describes the VET strategies of both the Federal Government and the federal state governments to reduce youth unemployment. Finally, special measures which aim to provide better vocational orientation for young people and improved matching of supply and demand on the training market are presented. (BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 1.2.2.4 Arbeitslosigkeit; L 5 Beratung & Orientierung; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; Berufsbildungspolitik; Duales System; Jugendarbeitslosigkeit; Beschäftigungsfähigkeit; Berufsorientierung; Durchlässigkeit im Bildungssystem; Dualer Studiengang